2014
DOI: 10.1136/postgradmedj-2014-132829
|View full text |Cite
|
Sign up to set email alerts
|

Clinic and ambulatory heart rates in patients with ischaemic heart disease and/or chronic heart failure taking rate-limiting medications: are they interchangeable?

Abstract: Background The prognostic benefit from heart rate (HR) reduction in patients with ischaemic heart disease (IHD) and/or chronic heart failure (CHF) is now firmly established. Most decisions regarding initiation and/or dose adjustment of HR-limiting medications in such patients are based on clinic HR. Yet, this is a highly variable parameter that may not necessarily reflect HR control over the 24 h period. Objective To examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…5) In a study assessing the agreement between the resting and 24-hour HR, despite a minimal difference and good correlation between the two measures, the limits of agreement were quite wide. 23) Thus, resting and 24-hour HR cannot be considered interchangeable. A recent study also found that up to 30% of patients with a low resting HR (< 70 bpm) had a high 24-hour HR ("75 bpm) based on Holter monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…5) In a study assessing the agreement between the resting and 24-hour HR, despite a minimal difference and good correlation between the two measures, the limits of agreement were quite wide. 23) Thus, resting and 24-hour HR cannot be considered interchangeable. A recent study also found that up to 30% of patients with a low resting HR (< 70 bpm) had a high 24-hour HR ("75 bpm) based on Holter monitoring.…”
Section: Discussionmentioning
confidence: 99%